Ordoliberalism: neither exclusively German nor an oddity. A review essay of Malte Dold's and Tim Krieger's Ordoliberalism and European Economic Policy: Between Realpolitik and Economic Utopia. - K. Horn (The Review of Austrian Economics, 2021)
The German intellectual tradition of ordoliberalism, a variant of neoliberalism particularly committed to a "functional and humane order," was long ignored in the Anglo-Saxon world. More recently, this has changed to some degree, especially under the impression of the European sovereign-debt crisis, during which Germany's insistence on rule-abiding behavior was critically attributed to the ordoliberal heritage. In the anthology edited by Malte Dold and Tim Krieger, ordoliberalism is discussed from many different angles, including the historical roots in the Freiburg School, the recent much-disputed strategies for dealing with the eurozone crisis, and a further development of the research program. The editors argue that scholarship in the spirit of ordoliberalism would benefit from being embedded within the interdisciplinary scientific cluster of Philosophy, Politics and Economics (PPE). The book makes a valuable contribution to a better-informed international discourse across the disciplines.
Keywords: B29; E61; P16; 330; Ordoliberalism; Freiburg school; European sovereign-debt crisis; PPE